The yoco from heaven is cultivated: perspectives on Paullinia yoco in airo-pai shamanism (western secoya-tucano) - Belaunde, Luisa Elvira (2008)
This article associates Airo-pai shamanistic vision and interpretation of dreams with their silvicultural management of yoco (Paullinia yoco), a wild vine rich in caffeine, endemic to the pleistocene refuge of Napo. According to Airo-pai ethnobotanic notions, yoco is a plantthat «gives advice» to those who intake it. From the analysis of a shamanic chant of yajé (Banisteriopsis caapi), myths and interpretation of dreams, we show how the management of this species is conceived from contrasting perspectives: for celestial beings, yoco is a domesticated plant that grows in the celestial gardens; for cuacuiyó (yoco’s «Master»), a seed-dispersing bird, yoco is its own plantation; and for terrestrial human beings, the collection of wild yoco is like hunting, associated in dreams with the nocturnal curassow (Nothocrax urumutum). This study thus illustrates the relevance of a perspectivist approach to understand the ethnobotanic lore underlying the management and extraction of a wild species of ritual and practical importance.